On a new family of generalized Bernstein operators - TALPĂU DIMITRIU , Maria (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this paper we remark that α-Bernstein operators, introduced by X. Y. Chen et al., are combinations of two known operators (Stancu and Bernstein operators) and we establish the preservation of global smoothness properties by these linear operators, the global smoothness being expressed by a Lipschitz condition with a certain second order modulus of continuity. Mathematics Subject Classification (2010): 41A36, 41A17. Received 27 June 2020; Accepted 29 August 2020.